The IT habits and mathematical experience base of the ’alpha generation’ in Hungary: Some results of an online questionnaire survey - Pintér, Marianna (Gyermeknevelés Tudományos Folyóirat, 2024)
In this article, I present some previously unpublished results of a research conducted in 2014-2019. The research consisted of two parts. The theoretical part is based on international and Hungarian literature. In this section, I investigated whether the conditions set forth in Károly (Karl) Mannheim’s generational theory are fulfilled in the case of children born in 2010 and after. The second part is an empirical part, in which I collected data about the IT device usage habits of the children in the indicated age group and their mathematical experience base before going to school. The method of data collection was a questionnaire survey. The first, pilot survey was a paper-based questionnaire that I posted to several kindergartens in Budapest in 2015. The questionnaire was voluntarily filled out anonymously by the relatives of 95 children. The answers highlighted that it is worth researching the topic. That is why I created an improved online questionnaire in 2018. The questionnaire was available nationwide, and it was filled out anonymously and voluntarily by the relatives of 345 Hungarian children.